2005
DOI: 10.1111/j.1439-0434.2005.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mycelial Growth Rates and RAPD‐PCR Profiles in a Population of Gaeumannomyces graminis var. tritici Originating from Wheat Plants Grown from Fungicide‐treated Seed

Abstract: Linear mycelial growth rates of 70 isolates of Gaeumannomyces graminis var. tritici on agar medium amended or unamended with the fungicide silthiofam were not correlated. Mycelial growth rate was not influenced by the fungicide applied to the seed of the plants from, which the isolates originated. DNA polymorphism determined by randomly amplified polymorphic DNA (RAPD) polymerase chain reaction was used to assess genetic variation among isolates. Thirty RAPD markers generated with five arbitrary 10-mer primers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…Application of molecular techniques to intraspecies variability studies makes it possible to find markers associated with various morphological or physiological traits [21][22][23][24]48]. In our study, four molecular markers (OPC-09b, OPC-08, OPJ-05 and GA-TCb) were found to be associated with growth rate at both temperatures tested.…”
Section: P-valuementioning
confidence: 71%
See 2 more Smart Citations
“…Application of molecular techniques to intraspecies variability studies makes it possible to find markers associated with various morphological or physiological traits [21][22][23][24]48]. In our study, four molecular markers (OPC-09b, OPC-08, OPJ-05 and GA-TCb) were found to be associated with growth rate at both temperatures tested.…”
Section: P-valuementioning
confidence: 71%
“…Our results indicate that there is a high level of genetic variation among the isolates examined. Cluster analysis using UPGMA was undertaken; this has been previously used to investigate pathogens infecting cereals [21][22][23][24]. Six groups resolved at 67% similarity level were represented on the dendrogram.…”
Section: P-valuementioning
confidence: 99%
See 1 more Smart Citation
“…DNA-based molecular markers are especially useful in plant breeding since these markers provide an efficient method for scoring segregating populations and identifying the desirable genotypes without waiting for the phenotypic expression of the gene (Brown et al 1996). As far as the ability of polymorphism detection is concerned, RAPDs are the most useful markers (Joshi and Nguyen 1993;Kuczynska et al 2001;Weber et al 2005). Being rapid, efficient and amenable to automation, RAPD markers have been proved to be effective for estimation of germplasm diversity (Virk et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Linkage between molecular markers and quantitative traits without use of a mapping population was also studied through methods such as logistic regression and discriminant analysis (Mcharo et al 2005), regression analysis (Javidfar et al 2006;Miano et al 2008), and two-sample comparison based on hypothesis testing Weber et al 2005;Irzykowska and Bocianowski 2008). All of these methods provide parametric models based on statistical hypothesis testing, which is commonly known to strongly depend on assumptions.…”
Section: Introductionmentioning
confidence: 99%